Precise measurement of trapping and manipulation properties of focused fractional vortex beams. Issue 8 (15th February 2022) - Gao, Binjie; Wen, Jisen; Zhu, Guiyuan; Ye, Linhua; Wang, Li-Gang
Abstract : Optical trapping and manipulation properties of focused fractional vortex beams are precisely measured and a clear picture of their trapping and rotation effects is presented. Abstract : Fractional vortex beams (FVBs) were believed to be hard to rotate microparticles at a half-integer topological charge due to the unique radial opening (low-intensity gap) in their intensity ring. However, recent research discovered more symmetric intensity structures with less intensity inhomogeneity of practical FVBs at the focal plane. Here, we experimentally demonstrated the manipulation of trapped microparticles and precisely measured their rotation periods at the focal plane of practical FVBs by using a high-speed camera. We verified that the measured orbital angular momentum (OAM) derived from the collective microparticle rotation is roughly proportional to the fractional OAM of practical FVBs. Furthermore, we also experimentally obtained the trapped microparticles' power spectra under the illumination of FVBs, from which we achieved the average trap stiffness to evaluate the two-dimensional trapping strength of the practical focused FVB intensity ring. Our results provide a new insight and an efficient tool on finely trapping and rotating microparticles and bio-cells by using fractional vortex beams.